Design of a Robust Sliding Mode Controller based on Nonlinear Modeling of Variable Speed Wind Turbine - Seyed Mahyar Mehdizadeh Moghadam; Alireza Khosravi; Seyed Mehdi Rakhtala Rostami (Majlesi Journal of Electrical Engineering, 2024)
In this article, the dynamic modeling of different electrical and mechanical parts of the nonlinear aerodynamics of variable speed wind turbine (DFIG) has been done. A high order sliding mode robust controller has been used to decrease the chattering effect in the presence of wind stochastic model, uncertainties of model dynamic error and mechanical power factor. The nonlinear robust control guarantees the performance and robust stability in order to reduce the effect of sliding instabilities and improve the turbine rotor speed changes for different angles of blade pitch. The simulation results confirmed the convergence of turbine rotor speed output and the improvement of tracking error in the presence of system uncertainties.